The Yersinia Yop Virulon: LcrV Is Required for Extrusion of the Translocators YopB and YopD - Sarker, Mahfuzur R. (American Society for Microbiology, 1998)
LcrV, an essential piece of the Yop virulon, is encoded by the large lcrGVsycDyopBD operon. In spite of repeated efforts, the role of LcrV in the Yop virulon remains elusive. In an attempt to clarify this, we engineered a complete deletion of lcrV in the pYV plasmid of Yersinia enterocolitica E40 and characterized the phenotype of the mutant. Complementation experiments showed that the mutation was not polar with regard to yopB and yopD. Nevertheless the mutation abolished secretion of YopB and YopD, while secretion of the other Yops was unaffected or even increased. Northern blot analysis showed that transcription of yopD was not affected. YopD could be detected inside the bacteria, showing that the lack of its secretion was not due to a lack of translation or to proteolysis. This indicated that LcrV is specifically involved in the process of release of YopB and YopD. We then investigated the possible interactions between LcrV and YopB or YopD. We constructed a glutathione S-transferase–LcrV hybrid protein, and we observed that either YopB or YopD could be copurified with it. The same approach showed that LcrV also interacts with LcrG but not with the chaperone SycD. Using deletants of lcrV, we then identified a definite LcrG-binding domain in the C terminus of LcrV.